Complementary and alternative medicine use among Iranian patients attending urban outpatient general practices. (February 2018) - Behnood-Rod, Azin; Afzali Poor Khoshkbejari, Masoomeh; Pourzargar, Pirouz; Hassanzadeh, Mostafa; Moharamzad, Yashar; Foroughi, Feizollah
Abstract: Objective: To determine the frequency of use of different types of CAM among patients who attended outpatient general practices (GP). Methods: CAM use, type, reason, administration, satisfaction, and disclosure to physician were documented by interviewing 360 patients. Results: A total of 192 individuals (53.3%) reported that they were using or had used at least one form of CAM therapy (a total of 343 CAM therapies). The five most commonly used CAM therapies were, respectively, vitamin supplements (105 subjects, 54.7%), traditional herbal products (80 cases, 41.7%), mineral supplements (58 cases, 30.2%), herbal medicines (49 cases, 25.5%) and dietary therapies (18 cases, 9.4%); 240 therapies (70%) were self-prescribed. Conclusion: A substantial number of the patients had used CAM on their own; one-third of these patients did not have sufficient knowledge about the therapies used. Health care providers should be aware of this practice by the patients and seek information about CAM usage.